International Perspectives on Terrorist Victimisation
XIV, 266 p.
Keywords: Considering an under-researched dimension of political violence, this interdisciplinary collection provides an extensive examination of terrorist victimisation. It explores how individual and public experiences of victimisation are constructed and how they are shaped by existing dynamics of violence.